Occurrence of polar stratospheric clouds as derived from ground-based zenith DOAS observations using the colour index - Lauster, Bianca; Dörner, Steffen; Enell, Carl-Fredrik; Frieß, Udo; Gu, Myojeong; Puķīte, Janis; Raffalski, Uwe; Wagner, Thomas (Atmospheric chemistry and physics, 2022)
Polar stratospheric clouds (PSCs) are an important component of ozone chemistry in polar regions. Studying the ozone-depleting processes requires a precise description of PSCs on a long-term basis. Although satellite observations already yield high spatial coverage, continuous ground-based measurements covering long time periods can be a valuable complement. In this study, differential optical absorption spectroscopy (DOAS) instruments are used to investigate the occurrence of PSCs based on the so-called colour index (CI), i.e. the colour of the zenith sky. Defined as the ratio between the observed intensities of scattered sunlight at two wavelengths, it provides a method to detect PSCs during twilight even in the presence of tropospheric clouds. We present data from instruments at the German research station Neumayer, Antarctica (71∘ S, 8∘ W), as well as Kiruna, Sweden (68∘ N, 20∘ E), which have been in operation for more than 20 years.